Bidirectional Coupler Study for Chip-Based Spectral-Domain Optical Coherence Tomography - Hong-Yan Zheng; Bo-Liang Chen; Hsiao-Yen Lu; Shih-Hsiang Hsu; Masanori Takabayashi (Micromachines, 2022)
A chip-based spectral-domain optical coherence tomography (SD-OCT) system consists of a broadband source, interferometer, and spectrometer. The optical power divider flatness in the interferometer’s wavelength is crucial to higher signal-to-noise ratios. A Mach–Zehnder directional coupler (MZDC) structure could be utilized to smoothly maximize the splitting ratio of 50:50 on a silicon platform, with a sub-micrometer of decoupler optical path difference insensitive to the process variation up to 20 nanometers. However, the optical signal reflected from the reference and sample will go back to the same interferometer MZDC. The so-called bidirectional coupler MZDC will not illustrate a flat optical power response in the operating wavelength range but could still demonstrate at least 20 dB signal-to-noise ratio improvement in OCT after the echelle grating spectrum compensation is applied. For maintaining the axial resolution and sensitivity, the echelle grating is also insensitive to process shifts such as MZDC and could be further utilized to compensate a 3 dB bidirectional MZDC structure for a broad and flat 100 nm wavelength response in the interferometer-based on-chip SD-OCT.